Avian Assemblage During the Development of Rice in Organic and Inorganic Rice Paddies and Its Relation to Insect Pests - Nattida Supahan* (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2022)
Birds play a vital role in rice cultivation as organisms that help maintain the ecological balance and help eliminate pests very effectively. However, various pests at each phase of rice growth, and the use of pesticides may cause differences in the bird species found in rice paddy. The objective of this research was to explore the species of birds found in organic rice paddy and inorganic rice paddy, and during each phase of rice growth, in Doi Kaew Subdistrict, Chom Thong District, Chiang Mai Province, Thailand. The bird data was collected between April and November 2018. Insects were also collected during each growth phase of rice to investigate the relationship with the number of birds found. There were 65 species found in the survey. Most of the birds were insectivores and belonged to Order Passeriformes. Birds found in the planted area were more similar to the organic rice paddy than the inorganic rice paddy. The values of Shannon Wienner’s diversity index (H’), Simpson’s index (λ), and Margalef’s index (D) of the planted area were at the highest level, followed by the inorganic rice paddy and organic rice paddy, respectively. Birds discovered in both paddies were statistically different (p<0.05), and the bird found during each phase of rice growth were statistically different (p<0.05). Even so, the birds that presented in each habitat were more similar to each other than other habitat types. The correlation between insectivorous birds and insect pests was positive in both rice paddy types, indicating that if there were more insect pests, there would be more birds as well. Keywords: bird diversity; rice cultivation; rice growth phase; pests; insectivorous birds *Corresponding author: Tel.: (+66)53885626 Fax.: (+66)53885626 E-mail: nattida_sup@cmru.ac.th